Macromedia flash-based interactive multimedia to increase elementary school students’ scientific literacy in natural and social sciences - AF Suryaning Ati MZ; Arfian Mudayan; Linaria Arofatul Ilmi Uswatun Khasanah; Wiwid Widiyanti (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2023)
The development of macromedia flash-based interactive multimedia aimed to increase students’ scientific literacy in the natural science subject material especially the characteristics of living things. This study used a 4D development model and employed a pretest-posttest control group design. The research data included the results of the validity, effectiveness of using macromedia flash-based interactive multimedia, and increasing students' scientific literacy after using macromedia flash-based interactive multimedia. The subjects of this study were fourth grade students at MI Muhammadiyah 1 Payaman, Lamongan. The validity consisted of material validity, design validity, and learning media validity from two experts. Meanwhile, the effectiveness of the media was perceived from the results of limited and field trials, as well as t-test and N-Gain test to investigate an increase in students’ scientific literacy. The product was tested on fourth grade students in science subjects. The results showed that the percentages of the validity test of learning materials, media design, instructional media were 98%, 945%, 91.25% respectively with very valid categories. The result of the t-test was 0.001 <0.05 with the N-Gain test results of 73.44%, meaning that there was a significant difference and an increase in students’ scientific literacy. It can be concluded that macromedia flash-based interactive multimedia is very suitable and effective as a medium for teaching natural sciences in elementary schools.